Effect of sodium stibogluconate in recruiting and awakening immune cells in the pleural fluid of pancreatic cancer: preparation for immunotherapy - Yu, Baofa; Jing, Peng; Gao, Feng; Zhang, Peicheng; Zheng, Guoqin; Zhang, Xiaomin (Frontiers in Immunology, 2024)
Ascites and pleural effusion are recognized complications of pancreatic cancer. These diseases are accompanied by ascites and pleural effusion, and drug treatment is limited by high costs, long hospital stays, and failure rates. Immunotherapy may offer new option, but in most patients with late stages of cancer, immune cells may lose the ability to recognize tumor cells, how to activate their immune cells is a major problem, sodium glucosidate (SSG) is injected into ascites as a protein tyrosine phosphatase inhibitor to wake up immune cells and prepare for immunotherapy. We used single-cell RNA sequencing (scRNA-seq) to investigate whether and how SSG injected into ascites of pancreatic cancer elicits an immune response. Our study showed that the process of SSG fusion treatment of ascites and pleural effusion, the interaction between TandNK cells, MPs cells, monocytes and neutrophils was induced, and large numbers of genes were expressed, resulting in upregulation of immune response, which also approved that SSG is not only used as a protein tyrosine phosphatase inhibitor, but also it works as a protein tyrosine phosphatase inhibitor. It can also be used to regulate immune cell function, recruiting immune cells to the right place with the help of PD-1 or PD-L1 to fight cancer cells in ascites and pleural effusions in cancer patients.